Response of CO2, N2O, and CH4 fluxes to contour tillage, diversion terrace, grassed waterway, and tile drainage implementation - Driscoll, Bryan A.; Krzic, Maja; Comeau, Louis-Pierre; Eskelson, Bianca N. I.; Li, Sheng (Frontiers in Soil Science, 2025)
In this study we evaluated CO2, N2O, and CH4 fluxes in two integrated best management practices (BMPIs) comprised of the following individual practices: diversion terraces (DT), grassed waterways (GW), and contour tillage (CT) [i.e., DTGW]; and DT, GW, CT, and tile drainage (TD) [i.e., DTGW+TD], relative to CT that served as a control. It was anticipated that due to its effects on soil water redistribution and soil temperature, diversion terraces and grassed waterways would influence the pattern of greenhouse gas (GHG) emission. This is the first study in the world linking such erosion control structures with subsurface drainage. Cumulative CO2 emissions were greatest in DTGW in both 2020 and 2021. In 2019, DTGW+TD N2O emissions were significantly lower than CT and DTGW. N2O emissions were highest in DTGW in 2020 and 2021, though not statistically significant. There were no significant differences in CH4 in any year. Soil in all BMPIs acted as a weak CH4 sink during the study period. This study demonstrated that the addition of TD to DT and GW significantly reduced the loss of stored carbon (as CO2) relative to undrained DT and GW, while also not emitting significantly more carbon than CT, in the initial years after implementation. Results were similar with respect to the loss of nitrogen, as N2O, where undrained DT and GW generally emitted more N2O in the first years after implementation.